Transparency in Regional Budget Management as a Context for Learning Public Administration - Daniel Tonu (Global Education Journal, 2026)
The transformation of governance in Indonesia after the reform era has placed information transparency as a key pillar of democracy. This study aims to evaluate the implementation of transparency and accountability principles in the management of the Regional Revenue and Expenditure Budget (APBD) of the East Nusa Tenggara (NTT) Provincial Government, referring to the standards of Law Number 14 of 2008. Using a descriptive qualitative research design with a case study approach, this study analyzes the entire budget cycle, including the planning, implementation, and reporting stages. The results show that although NTT Province consistently obtains Unqualified Opinions (WTP), the effectiveness of substantial transparency is still hampered by technical constraints in the Regional Government Information System (SIPD) and limited accessibility of real data to the wider public. Administratively, the main obstacles include uneven digital infrastructure and low digital literacy among civil servants. Politically, the dynamics of budget negotiations and pressures on Regional Original Revenue (PAD) targets often limit information disclosure at crucial stages. The theoretical contribution of this study broadens the discourse on digital bureaucracy in underdeveloped regions, while its practical contribution provides recommendations for strengthening the Information and Documentation Management Officer (PPID) and integrating participatory oversight systems. Limitations of this study include the difficulty of accessing unpublished internal meeting data.